Adult Students' Perceptions of a Synchronous Distance Education Teacher Training Programme Using Microsoft Teams - Anna Marina Sarma; Pinelopi Gkila; Stephanos Armakolas (Flexible Learning Association of New Zealand, 2023)
This qualitative survey studies the perceptions of adult students enrolled in a teacher training programme in Greece. It examines synchronous distance education, the Microsoft Teams platform, and the prospect of strengthening and establishing this type of education after the COVID-19 pandemic. The survey used the semi-structured interview as a basic tool to gather students' perceptions of the teacher training programme, "EPPAIK". The results show that the benefits to the user of synchronous distance education, and the possibilities provided by the Microsoft Teams platform, are many. Most respondents consider it necessary to evaluate contemporary education, to establish a combination of both traditional and contemporary educational practices (hybrid learning/education), to achieve the best results in the future.